PETCO2 measured by a new lightweight mainstream capnometer with very low dead space volume offers accurate and reliable noninvasive estimation of PaCO2 - Takahashi D; Hiroma T; Nakamura T (Dove Medical Press, 2011)
Daijiro Takahashi, Takehiko Hiroma, Tomohiko NakamuraDivision of Neonatology, Nagano Children’s Hospital, Nagano, JapanObjective: Although capnometers are widely used in adult and pediatric intensive care units, they are not widely used in neonatal intensive care units due to issues such as the weight of sensors, dead space, and leakage from tracheal intubation tubes. These authors developed a light and low dead space airway adaptor of end-tidal carbon dioxide pressure (PETCO2) and evaluated the correlations between PETCO2 and partial CO2 pressure (PaCO2) in rabbits while changing tidal volume and leakage volume.Methods: Firstly, Japanese rabbits weighing 2 kg were divided into three tidal volumes (6 mL/kg, 10 mL/kg, or 15 mL/kg), and PETCO2 and PaCO2 were measured. Secondly, the respiratory apparatus was set to a tidal volume/body weight ratio of 10 mL/kg, leakage rates were divided into seven groups, and PETCO2  and PaCO2 were measured.Results: PETCO2 and PaCO2 were significantly correlated (r2 = 0.9099, P < 0.0001) when there was no leakage in the tracheal intubation tubes. No significant differences were observed between PaCO2 and PETCO2 (Pa-ETCO2) in the three tidal volume/body weight groups or for groups in which leakage rate was <60%, but significant deviations in Pa-ETCO2 were noted in groups with leakage rate 60%.Conclusion: There was a strong correlation between PETCO2 and PaCO2 when tidal volume/body weight ratio was 6–15 mL/kg with leakage rate <60%. Lightweight mainstream capnometer with a low amount of dead space airway adaptor might be useful in very low birth weight infants with small tidal volume.Keywords: capnography, mainstream, neonate